Mitochondrial Voltage-Dependent Anion Channel Protein Por1 Positively Regulates the Nuclear Localization of Saccharomyces cerevisiae AMP-Activated Protein Kinase - (:unkn) unknown (My University, 2018)
ABSTRACT Snf1 protein kinase of the yeast Saccharomyces cerevisiae is a member of the highly conserved eukaryotic AMP-activated protein kinase (AMPK) family, which is involved in regulating responses to energy limitation. Under conditions of carbon/energy stress, such as during glucose depletion, Snf1 is catalytically activated and enriched in the nucleus to regulate transcription. Snf1 catalytic activation requires phosphorylation of its conserved activation loop threonine (Thr210) by upstream kinases. Catalytic activation is also a prerequisite for Snf1’s subsequent nuclear enrichment, a process that is mediated by Gal83, one of three alternate β-subunits of the Snf1 kinase complex. We previously reported that the mitochondrial voltage-dependent anion channel (VDAC) proteins Por1 and Por2 play redundant roles in promoting Snf1 catalytic activation by Thr210 phosphorylation. Here, we show that the por1Δ mutation alone, which by itself does not affect Snf1 Thr210 phosphorylation, causes defects in Snf1 and Gal83 nuclear enrichment and Snf1’s ability to stimulate transcription. We present evidence that Por1 promotes Snf1 nuclear enrichment by promoting the nuclear enrichment of Gal83. Overexpression of Por2, which is not believed to have channel activity, can suppress the localization and transcription activation defects of the por1Δ mutant, suggesting that the regulatory role played by Por1 is separable from its channel function. Thus, our findings expand the positive roles of the yeast VDACs in carbon/energy stress signaling upstream of Snf1. Since AMPK/Snf1 and VDAC proteins are conserved in evolution, our findings in yeast may have implications for AMPK regulation in other eukaryotes, including humans. IMPORTANCE AMP-activated protein kinases (AMPKs) sense energy limitation and regulate transcription and metabolism in eukaryotes from yeast to humans. In mammals, AMPK responds to increased AMP-to-ATP or ADP-to-ATP ratios and is implicated in diabetes, heart disease, and cancer. Mitochondria produce ATP and are generally thought to downregulate AMPK. Indeed, some antidiabetic drugs activate AMPK by affecting mitochondrial respiration. ATP release from mitochondria is mediated by evolutionarily conserved proteins known as voltage-dependent anion channels (VDACs). One would therefore expect VDACs to serve as negative regulators of AMPK. However, our experiments in yeast reveal the existence of an opposite relationship. We previously showed that Saccharomyces cerevisiae VDACs Por1 and Por2 positively regulate AMPK/Snf1 catalytic activation. Here, we show that Por1 also plays an important role in promoting AMPK/Snf1 nuclear localization. Our counterintuitive findings could inform research in areas ranging from diabetes to cancer to fungal pathogenesis.
Keywords: AMPK/Snf1; VDAC; mitochondria; nuclear localization; yeast